TREATMENT AND USE OF PESTICIDES IN SHALLOT CULTIVATION IN CIREBON REGENCY: Key words: treat, pesticides, shallots - Valeriana Darwis; Chairul Muslim; Iwan Setiaji Anugrah (Journal of Food System & Agribusiness, 2021)
Productivity of shallots is influenced by the use of production inputs, including the use of pesticides. This study aims to see a portrait of the behavior and use of pesticides in onion cultivation in Cirebon Regency. The location was purposely selected with consideration as the shallot producing center. The survey was conducted in the first week of September 2020. The primary data collection was carried out by direct interviews with respondents using a questionnaire. The selection of respondents employed a random sampling technique. The collected data were analyzed using quantitative descriptive analysis. From the results of the analysis, it can be seen that: (i) 25% of farming costs are used to buy pesticides, (ii) 64% of farmers buy pesticides for controlling pests and diseases attack, (iii) 36% of farmers read labels on pesticide packages and 45 % of farmers read the pesticide spraying manual. (iv) 68% of farmers use pesticides exceeding the recommended dose and 77% of farmers mix 2 to 3 brands in dealing with pests and diseases. In order to maintain the health of farmers, not to damage the environment, and to buy pesticides as needed, it is suggested that the Integrated Pest Control Field School Program needs to be re-implemented.